Marker Assisted Selection for Bacterial Leaf Blight Rice Mutant Lines Resistant - A. Aryanti; A. Almaida; Rika Heryani; Nana Supriatna (Indonesian Journal of Biotechnology, 2015)
Induction of mutation using gamma rays for improving of Mira-1 rice variety has been conducted.Rice mutant lines M2 generation have been obtained from mutation by the doses of 25, 50, 75, 100, 150 and200 Gy of gamma rays. Selection of mutant lines tolerant to the disease was only observed in the field neithergenetically. Marker assisted selection is a tool to obtain a new rice variety tolerant to the disease of bacterialleaf blight (BLB) genetically. Xanthomonas oryzae pv.oryzae (Xa) was the pathogen of BLB, and the identificationof rice mutant lines which were containing of Xa5, Xa13 and Xa21 genes have been done using PolymeraseChain Reaction ( PCR ) method. The result showed that one mutant line, and four mutant lines from mutationby the doses of 25 Gy and 150 Gy were containing Xa5, Xa13 and Xa21 genes the same as that of Code ricevariety as positive control, and none in Kencana Bali rice variety as negative control. Mira-1 rice variety as theparent plant was only contains Xa5 and Xa21 genes. The doses of 50 Gy and 100 Gy were very affective onremoving of all bands for identification of those genes. The purpose of this research was to obtain the mutantlines which were contain of those Xa genes as indicator for resistant to BLB disease genetically.